اتجاهات الشباب الجامعي نحو المال من منظور سوسيولوجي (El-Wahat Journal for Research and Studies, 2021)
Money Can Be Considered A Natural Birth Of Development Work; Production Forces And Interactive Relationship, Money Began As A Value And Means To Achieve The Human Needs Being, Economists And Other Researchers And Thinkers Agreed That Money Is A Repository Of Value, It Is A Tool With Purchasing Power Or According To The Expression Of Economists Money Is A Measure Of All Values And An Intermediary For Exchange. However, The Modern Forms Of Exchange Have Made Money In Its Various Forms Valuable To The Degree To Which It May Turn Away From Its Nature To The Goal.        But Money Is Also A Very Important Social Institution That We Want To Study In This Research By Analyzing The Attitudes Of Youth Towards Money. Keywords- Sociology Of Money, Youth, Likert Scale , Money, Consumption, Tabu, Georg Simmel